2021
DOI: 10.1155/2021/6644093
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Protective Effect of Chinese Herbal Prescription, Yiqi Jiedu Decoction, on Testis in Mice with Acute Radiation Injury

Abstract: Objective. A Chinese herbal prescription, Yiqi Jiedu (YQJD) decoction, is used for injuries caused by radiotherapy. This study aimed to investigate the dynamic protective effects of YQJD decoction in mice on radiation damage at different time points of the testis. Methods. The 200 male Balb/c mice were randomly divided into 5 groups (blank, model, Anduolin, low-dose YQJD, and high-dose YQJD groups). Blank and model groups were all given stomach deionized water. Anduolin group and high and low dose of Chinese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, damage during any phase affects spermatogenesis. The spermatogenic cycle of male mice last approximately 35 days, at which time spermatogonia begin to recover and new spermatogenic cells appear [ 34 ]. In our study, the structure of the seminiferous tubules in IR-treated mice, including the widened interstitial space, the decreased number of interstitial cells, and the serious vacuolation, had not recovered on the 35th day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, damage during any phase affects spermatogenesis. The spermatogenic cycle of male mice last approximately 35 days, at which time spermatogonia begin to recover and new spermatogenic cells appear [ 34 ]. In our study, the structure of the seminiferous tubules in IR-treated mice, including the widened interstitial space, the decreased number of interstitial cells, and the serious vacuolation, had not recovered on the 35th day.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf, L. barbarum L, G. lucidum Karst, and Astragalus mongholicus Bunge exerted radioprotective effects by improving the survival of irradiated mice by reducing radiation-induced injury of the immune system. 91 Qi tonification and toxin removal induced by Chinese herbal medicines can reduce the recovery time after complete blood cell inhibition and reduce radiation-induced mortality in mice, 92 and Yiqi and Yangyin formulas were shown to improve the survival rate of mice exposed to sublethal doses of TBI by reducing intracellular ROS levels in hematopoietic cells. 93 Collectively, these studies have demonstrated that Chinese herbal medicines exert protective effects against acute radiation injury in various tissues, and their advantages may be related to the reduction in continuous tissue damage caused by radiation exposure and the promotion of subsequent recovery.…”
Section: Chinese Herbal Medicinesmentioning
confidence: 99%
“…Wolf, L. barbarum L, G. lucidum Karst, and Astragalus mongholicus Bunge exerted radioprotective effects by improving the survival of irradiated mice by reducing radiation‐induced injury of the immune system 91 . Qi tonification and toxin removal induced by Chinese herbal medicines can reduce the recovery time after complete blood cell inhibition and reduce radiation‐induced mortality in mice, 92 and Yiqi and Yangyin formulas were shown to improve the survival rate of mice exposed to sublethal doses of TBI by reducing intracellular ROS levels in hematopoietic cells 93 …”
Section: Advancement In the Development Of Radioprotective Agentsmentioning
confidence: 99%